Ecodiseño y producción sostenible de vajilla biodegradable para un modelo de emprendimiento ecológico en el CAMPUS CEASA. - Vásquez Mackenzie, Jhoselyn Mercedes (2020)
The objective of this research project was to design an ecological entrepreneurship model to produce biodegradable dishes, generating profitability and helping the environment in the process. To develop Ecodesign processes, was used a program called Pilot ecodesign this was based on the practical implementation of Ecodesign. It was given an ecological entrepreneurship approach and quality products were generated for the University community. Developing a novel project that has economic strength and environmental sustainability. An entrepreneurial model was built that developed the production of biodegradable tableware at the Technical University of Cotopaxi CEASA campus. With the construction of the biodegradable tableware, the entrepreneurship model determined the characteristics and stages that should be followed for the elaboration of the model. By generating an ecological entrepreneurship model, the goal is to mitigate possible damage to the environment and damage to people's health. Making a comparative table of different entrepreneurship models, the most optimal model for the research project was found, which was the RedMer Model, because it is characterized as an innovative model and focuses exclusively on environmental improvement. Subsequently, opinion polls were conducted in which 98% of the University community suggest that an internal regulation within the CEASA campus is necessary for the reduction of the use of plastics especially of expanded polystyrene that is not recycled since it is one of the pollutants most prominent in the surroundings of the University. The students and people around the Technical University of Cotopaxi CEASA campus.